Financial Globalization and Fiscal Perfomance in Emerging Markets - Hauner, David (IMF Working Papers; Working Paper, 2005)
In recent years financial globalization and benign global market conditions have helped emerging markets in their external financing and budgetary positions. This paper examines three related issues: (i) the importance of the impact of the benign financial environment on fiscal performance; (ii) the likely fiscal impact of a reversal in this environment; and (iii) the potential contribution of fiscal reforms to maintaining favorable market access. The results suggest that the benefits from the benign environment have been substantial and that the potential reversal of the favorable external conditions underlines the need for further fiscal reforms.